PELANGGARAN TERHADAP DESAIN TAS PT BATIK KERIS INDONESIA BERDASARKAN UU NO.31 TAHUN 2000 - Fiona Natania; Gunardi Lie; Moody Rizqy Syailendra P. (PROSIDING SERINA, 2021)
This research was conducted with the aim of knowing how to protect industrial design rights and dispute resolution mechanisms in the industrial design field within the legal framework of Intellectual Property Rights based on Law UU 31 / 2000 concerning about Industrial Design. This research method used by researchers is a normative juridical approach and it can be concluded that there are still many issues and disputes related to Industrial Design. With the enactment of the Industrial Design Law, the Government of Indonesia seeks to protect Industrial Design rights holders from various forms of violations such as imitation/plagiarism as well as assisting in preventing and resolving disputes in the Industrial Design field. In this study, the problem occurred between PT. Batik Keris Indonesia objected to the issuance of Wenny Sulistiowati's Industrial Design certificate. From the results of the study, it can be concluded that the registered industrial design must have an element of novelty in accordance with UU 31 / 2000 (2) of the Industrial Design Law.